2007
DOI: 10.1177/0363546506293702
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Surfing Injuries

Abstract: There were 13 acute surfing injuries per 1000 hours of competitive surfing. The risk of injury was more than doubled when surfing in large waves or over a hard seafloor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 12 publications
(21 reference statements)
2
52
1
1
Order By: Relevance
“…The injury rate found was 5.7 per 1000 athlete exposures, or 13 per 1000 h of competitive surfing, with 6.6 significant injuries per 1000 h of competitive surfing. This injury rate compares favorably to those found in American collegiate football (33 per 1000 h), soccer (18 per 1000 h), and basketball (9 per 1000 h) where similar methods of data collection and injury definition were used [43]. The relative injury risk was calculated to be 2.4 times greater when surfing in waves overhead or bigger and 2.6 times greater when surfing over a rock or reef bottom.…”
Section: Specific Extreme Sports and Their Associated Injuriesmentioning
confidence: 79%
“…The injury rate found was 5.7 per 1000 athlete exposures, or 13 per 1000 h of competitive surfing, with 6.6 significant injuries per 1000 h of competitive surfing. This injury rate compares favorably to those found in American collegiate football (33 per 1000 h), soccer (18 per 1000 h), and basketball (9 per 1000 h) where similar methods of data collection and injury definition were used [43]. The relative injury risk was calculated to be 2.4 times greater when surfing in waves overhead or bigger and 2.6 times greater when surfing over a rock or reef bottom.…”
Section: Specific Extreme Sports and Their Associated Injuriesmentioning
confidence: 79%
“…In the present study, it was used an Adapted Semi Structured Questionnaire 2 , 11 in order to identify and analyze the prevalence of the most common injuries in male surfers, in the seacoast of Paraná, subdivided into professional, amateur and recreational categories. The results of this study showed that 70% of the sample subjects were recreational surfers, 28% amateurs and 2% professional (a single surfer).…”
Section: Discussionmentioning
confidence: 99%
“…Data collection was performed using a Adapted Semi-Structured Questionnaire 2 11 . which included the following items: email, age, surf practice category (professional, amateur or recreational), 4 characteristics of surf practice (time of practice, frequency, hours per day), duration and type of exercise performed before and/or after the activity (stretching or heating), type of injury caused by sport (laceration-cut; contusion-hit; fracture-bone fracture, dislocation-articulation dislocation; joint sprain- joint twist; muscle or ligament injury; burns), as well as the anatomic region injured (head/neck; torso; arms; legs and feet).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated incidence of surfing-related injuries is 3.5 to 6.6 per 1000 days [2, 3]. Consequently, health care professionals are likely to encounter patients with surfing-associated trauma.…”
Section: Introductionmentioning
confidence: 99%